Coping with global environmental change, disasters and security threats, challenges, vulnerabilities and risks - Brauch, Hans Günter (Hexagon series on human and environmental security and peace, 2011)
This policy-focused Global Environmental and Human Security Handbook for the Anthropo-cene (GEHSHA) addresses new security threats, challenges, vulnerabilities and risks posed by global environmental change and disasters. In 6 forewords, 5 preface essays 95 peer reviewed chapcountries analyse in 10 parts concepts of military and political hard security and economic, social, environmental soft security with a regional focus on the Near East, North and Sub-Sahara Africa and Asia and on hazards in urban centres. The major focus is on coping with global environmental change: climate change, desertification, water, food and health and with hazards and strategies  on social vulnerability and resilience building and scientific, international, regional and national political strategies, policies and measures including early warning of conflicts and hazards. The book proposes a political geo-ecology and discusses a "Fourth Green Revolution" for the Anthropocene era of earth hist